EFEKTIVITAS PENDIDIKAN GIZI DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN GIZI ANAK SD - Zulaekah, Siti (Jurnal Kesehatan Masyarakat, 2012)
Pendidikan gizi pada anak anemia di sekolah dasar diberikan dengan harapan pengetahuan gizi dan pola makan anak akan berubah sehingga asupan makan terutama asupan besi dan kadar hemoglobin anak akan meningkat. Penelitian ini bertujuan mempelajari efek pendidikan giziÃÂ  terhadap perubahan pengetahuan gizi anak sekolah dasarÃÂ  yang anemia.Penelitian ini merupakan penelitian quasyÃÂ  experiment denganÃÂ  rancangan pretest post-testÃÂ  controlÃÂ  group. PenelitianÃÂ dilakukanÃÂ  terhadapÃÂ  36ÃÂ  sampel.ÃÂ  PendidikanÃÂ  giziÃÂ  secaraÃÂ  komprehensifÃÂ  dengan alat bantu booklet pada anak, orang tua dan guru kelas. Pendidikan gizi pada anak diberikan dua minggu sekali, sedangkan pada guru kelas dan orang tua diberikan empat mingguÃÂ  sekali dalam 12 minggu. Pengetahuan gizi pada sampel mengalami peningkatanÃÂ  (17,44 point). SecaraÃÂ  statistik ada perbedaan bermakna pengetahuan gizi anak SD yang anemia sebelum dan sesudah inter-vensi (p=0,0001). ÃÂ  ÃÂ  Abstract ÃÂ  Nutrition education for anemiaÃ¢â¬â¢s children in elementary schools are given the hope that knowledge about nutrition and diet of children is changed so that the intake ofÃÂ  food,ÃÂ  especiallyÃÂ  theÃÂ  intakeÃÂ  ofÃÂ  ironÃÂ  and hemoglobin ÃÂ levels ÃÂ ofÃÂ  children willÃÂ  increase. This research aims at studying the effects of nutrition education to changes in nutritional knowledge of elementary school children who anemia. This wasÃÂ ÃÂ  a research experiment with the design quasy pretest post-test control group. Research carried out on 36 samples. Nutrition education in a comprehensive booklet with tools for children, parents and classroom teachers. Nutrition education in children are given every two weeks, while the class teacher and parents are given every four weeks in 12 weeks. Knowledge of nutrition in the sample experienced an increase (17,44 point). Statistically significant differences of nutrition knowledge of elementary school children whose anemia before and after intervention (p= 0,0001).Keywords:Education nutrition; Anemia; Elementary schools children; Knowledge of nutrition